2018
DOI: 10.21315/tlsr2018.29.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Physicochemical Characteristics of Raw Goat Milk Collected from Different Farms in Malaysia

Abstract: This study was conducted to determine the physical and chemical composition of goat milk produced by eight local farms located in the central region of Malaysia. Farms 1 to 4 (F1-SC, F2-SP, F3-SP, F4-SBC) reared Saanen-type goats while farms 5 to 8 (F5-JK, F6-JPEC, F7-JTC, F8-JC), Jamnapari-type goats. The common feedstuffs used in all farms comprised of fresh or silage from Napier grass, feed pellets, and brans while two farms, F5-JK and F6-JPEC supplemented the feeds with soybean-based product. The total sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
12
0
2
Order By: Relevance
“…In our sample, we registered average rates in milk of 3.584% protein, 5.279% fat and a dry extract of 14.454%. These are slightly higher percentages than those found for Saanen or Anglo-Nubian dairy goats (Dami an et al 2008), and similar to those for the Jamnapari Koplo breed (Jaafar et al 2018). Deroide et al (2016) found slightly lower average values for both milk yield and milk components and moderately lower variation coefficients for Murciano-Granadina goats.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In our sample, we registered average rates in milk of 3.584% protein, 5.279% fat and a dry extract of 14.454%. These are slightly higher percentages than those found for Saanen or Anglo-Nubian dairy goats (Dami an et al 2008), and similar to those for the Jamnapari Koplo breed (Jaafar et al 2018). Deroide et al (2016) found slightly lower average values for both milk yield and milk components and moderately lower variation coefficients for Murciano-Granadina goats.…”
Section: Discussionsupporting
confidence: 69%
“…In the case of the farm, some authors have ascribed this stronger effect to climate variations at a certain location, the nutritional quality of food provided to animals and herd composition (Jaafar et al 2018). Unlike in the study by Jaafar et al (2018), we assess a single breed, so that, the differences in the composition of goat milk samples between farms could be rather determined by factors such as the diet given to goats at first instance ( Supplementary Table S5). Simultaneously, our CATREG standardised coefficients (b) for the effect of farms and age were positive, moderate to high and statistically significant for milk yield and all components.…”
Section: Discussionmentioning
confidence: 99%
“…Fat content is influenced by the quality and quantity of feeds, genetics, and the stage of lactation (Getaneh et al, 2016). Digestible fibre contained in the feeds increases the acetic acid availability for milk fat synthesis and stimulates energy partitioning towards milk synthesis instead of body fat reserve deposition (Jaafar et al, 2018). Protein content was classified into a good grade according to Thai Agricultural Standard.…”
Section: The Quality Of Raw Goat Milkmentioning
confidence: 99%
“…Protein content in goat milk is affected by protein content in the feeds. Feed with high protein content contributes to the increasing of milk protein content (Jaafar et al, 2018). Usually, concentrate becomes the source of protein for goat.…”
Section: The Quality Of Raw Goat Milkmentioning
confidence: 99%
“…Such variable patterns could be attributed to the conglomerate of factors that the farm involves as a factor itself. In these regards, some authors have suggested climatic variations at a given place, farm management policies (traditional, intermediate or modern), altitude (plains, hills, mountains), farm size (small, medium, large), the nutritional quality of the feed provided to the animals or the composition of the herd (Jaafar et al 2018;Vacca et al 2018) may presumably be some of the factors on which the differences reported for our results may base. For instance, in the case of somatic cells, the size of the farm and the composition of the herd may have been decisive as, under confined animal conditions, typical of intensive systems, animals are both more exposed to intramammary infections and to a greater likelihood of large scale transmission by direct contact between animals (Lôbo et al 2017).…”
Section: Discussionmentioning
confidence: 68%